Mechanisms and mitigation of agglomeration during fluidized bed combustion of biomass: A review. (15th October 2018) - Morris, Jonathan D.; Daood, Syed Sheraz; Chilton, Stephen; Nimmo, William
Highlights: Mechanisms, effects of variables, and prediction of agglomeration were reviewed. Two principal mechanisms of agglomeration: coating-induced and melt-induced. Temperature, fuel, bed material, and additives are key for agglomeration control. An overview of predicative methods is given, with signposting to recent reviews. Abstract: A key issue associated with fluidized bed combustion of biomass is agglomeration. The presence of high quantities of alkali metal species in biomass ash leads to the formation of sticky alkali silicate liquid phases during combustion, and consequently the adhesion and agglomeration of bed material. This review examines probable mechanisms of agglomeration and the effects of operational variables in reducing its severity. Additionally, an overview of monitoring and prediction of agglomerate formation is given. Two key mechanisms of agglomeration are apparent in literature, and both may occur concurrently dependending on fuel composition. Coating-induced agglomeration is defined by the interaction of alkali metals in fuel ash with silica in the bed material to form an alkali silicate melt. Melt-induced agglomeration is defined by the presence of sufficient amounts of alkali metals and silica in the fuel ash which together form a eutectic melt. Physical mechanisms, such as tumble agglomeration and sintering, may further enhance either of the coating-induced or melt-induced mechanisms. Of the operational variables examined in this review, temperature, fluidizing gas velocity, fuel, bed material and additives have been shown to have the greatest effect on agglomeration severity. Prediction of agglomeration propensity may be attempted with mathematical correlations or lab-scale fuel testing before use in the boiler, or with in-situ methods, which are typically focused on temperature or pressure analysis. The review of the literature has highlighted the need for further research in several areas, including: mechanisms when using alternate bed materials, use of dual-fuel biomass blends, technical and economic optimisation of the use of alternative bed materials and additives, and further modelling of coating growth behaviours.